A comparative study between preoperative intraincisional coamoxiclav infiltration and intravenous coamoxiclav injection for prevention of surgical site infection - Neniwal, Vishal Kumar; Chohan, Pooja; Neniwal, Nitin; Sharma, Rakesh Kumar; Meena, Ramgopal (International Surgery Journal, 2025)
Introduction: Infection remained a great problem in surgical practice. Infection is encountered by all surgeons by the nature of their craft; they invariably impair the first line of host defense. It happens to be one of the major causes of post-operative morbidity and mortality. Intraincisional antibiotic injection should be beneficial in two ways; very high wound levels will prevent wound sepsis, and good serum levels will minimize systemic complications. Methods: This is a prospective randomized controlled study comprising of 200 patients divided in to two groups i.e. 100 in each group. Group A-Preoperative intraincisional infiltration of 1.2g Coamoxiclav dissolved in 20 ml of 0.9% saline solution will be infiltrated along the skin and the subcutaneous tissue in the proposed line of incision, 20 minutes before surgical incision. Group B-Preoperative administered a single dose of 1.2 g Coamoxiclav intravenously just before the induction of anaesthesia. Result: Overall incidence of SSI in Group A was 1% and in Group B 6%. Overall average time for complete healing in group A less than group B. Frequency of infection due to gram negative bacteria was more as compared to gram negative in the cases that developed SSI. Conclusion: The incidence of SSI was lower in the group of patients who were subjected to preoperative intraincisional Coamoxiclav infiltration as compared to the group who received preoperative intravenous Coamoxiclav. There was statistically significant relation between the types of wounds, duration of surgery to the development of SSI in this study.